Human-hand-imitated prostate particle implantation robot and using method thereof - LI BING; ZHANG YONGDE (2021)
The invention discloses a human-hand-imitated prostate particle implantation robot and a using method thereof, and belongs to the technical field of medical equipment. The robot solves the problems that an existing robot for conducting prostate radioactive particle implantation operation is difficult to meet the requirement for a flexible multi-posture needle inserting task, and a flexible obstacle avoiding task cannot be conducted. A single-dimensional force sensor and a displacement sensor are installed on movement mechanisms; a six-dimensional force sensor is installed between a particle implantation mechanism and the tail end of a human-hand-imitated mechanical arm, and human-hand-imitated actions are conducted through a first movement mechanism, a second movement mechanism, a third movement mechanism and a fourth movement mechanism; a puncture assembly and the fourth movement mechanism are fixedly connected through a main support; an inner needle assembly is located between the puncture assembly and the